2019
DOI: 10.1097/psy.0000000000000664
|View full text |Cite
|
Sign up to set email alerts
|

Facial Emotion Recognition Abilities in Women Experiencing Eating Disorders

Abstract: OBJECTIVE: Impairments in facial emotion recognition are an underlying factor of deficits in emotion regulation and interpersonal difficulties in mental disorders and are evident in eating disorders (EDs). METHODS: We used a computerized psychophysical paradigm to manipulate parametrically the quantity of signal in facial expressions of emotion (QUEST threshold seeking algorithm). This was used to measure emotion recognition in 308 adult women (anorexia nervosa [n = 61], bulimia nervosa [n = 58], healthy contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 53 publications
1
18
0
Order By: Relevance
“…Krejtz et al (2020) found a marginal, non-significant effect for response times during the categorization of morphed neutral to happy, angry and sad expressions. In the present study, we explicitly instructed our observers to favour accuracy rather than speed, in order to conform to our previous studies comparing different populations (e.g., Richoz et al, 2018;Rodger et al, 2015;Rodger et al, 2018;Wyssen et al, 2019) and the large majority of the literature in affective science. As such, response times could not be analysed here.…”
Section: Discussionmentioning
confidence: 99%
“…Krejtz et al (2020) found a marginal, non-significant effect for response times during the categorization of morphed neutral to happy, angry and sad expressions. In the present study, we explicitly instructed our observers to favour accuracy rather than speed, in order to conform to our previous studies comparing different populations (e.g., Richoz et al, 2018;Rodger et al, 2015;Rodger et al, 2018;Wyssen et al, 2019) and the large majority of the literature in affective science. As such, response times could not be analysed here.…”
Section: Discussionmentioning
confidence: 99%
“…The findings are less consistent when assessing emotion recognition of others (ToM). Thus, deficits in emotion recognition of others have been found in some studies of patients with AN (Harrison et al, 2009), but not in others when applying ToM measures (Bentz et al, 2017) or other paradigms (e.g., Wyssen et al, 2019).…”
Section: Introductionmentioning
confidence: 96%
“…They found that children with ADHD were less sensitive to both positive and negative emotions. Another study by Wyssen et al (2019) used the Difficulties with Emotion Regulation Scale (DERS), developed by Gratz and Roemer (2004), to compare recognition of negative emotions among women experiencing eating disorders with ER among healthy women and women experiencing mood and anxiety disorders. These studies contribute to our understanding of social cognitive challenges in clinical populations.…”
Section: Existing Er Assessmentsmentioning
confidence: 99%